The Difference between Chronic Myeloid Leukemia before and during the COVID-19 Pandemic: A Retrospective Study from Dharmais Cancer Center - Tadjoedin, Hilman; Suryana, Kresna Dharma; Hadisantoso, Dwi Wahyunianto; Siregar, Nia Novianti; Djamal, Rizky Syawaluddin; Setiawan, Lyana; Hartono, Bryan Arista; Kunigara, Manika Putri (Indonesian Journal of Cancer, 2025)
Background: Chronic myeloid leukemia (CML) is a rare disease, with a global incidence rate ranging from 10 to 15 cases per 1,000,000 population annually, constituting approximately 15% of all adult leukemia. The achievement of complete response in CML patients has been affected by the COVID-19 pandemic. This study aimed to determine differences in characteristics, survival, and complete hematological response (CHR) in CML patients before and after the COVID-19 pandemic at Dharmais Cancer Hospital.Method: A cohort retrospective was conducted using medical records among CML patients diagnosed and treated in 2018 to 2022 in Dharmais Cancer Hospital. Demographic, characteristics, and survival were described. Overall survival was analyzed using Kaplan-Meier and log-rank test, and bivariate analysis was used with the Chi-square and Fisher's exact test. Patients aged 18 years with CML confirmed by bone marrow analysis, and detected fusion of BCR-ABL were included, and multiple malignancies were excluded.Results: The study was conducted on 108 subjects (56 vs. 52, before and during the pandemic, respectively). The demographic characteristics in both periods showed that the majority of subjects were male (59.8% vs. 40.2%), had normal BMI (58.1% vs 41.9%), and had no comorbidities. However, there was a difference in age distribution. The subjects before the pandemic were predominantly over 40 years, while those during the pandemic were 18-39 years. A total of 91/108 subjects survived (49.5% before vs. 50.5% during the pandemic). The median overall survival was 55 vs. 52 months, with a p-value of 0.173. No significant association was found between the study period or history of COVID-19 infection and CHR. However, a significant association was observed between the CML phase and outcomes.Conclusion: No significant differences were observed in demographic or clinical characteristics, overall survival, or CHR among CML patients before and during the COVID-19 pandemic.